Penentuan Daerah Rawan Kebakaran dengan Sistem Informasi Geografik (Kasus Pooncarie Region, New South Wales, Australia) - Rochmad Muryamto (Forum Teknik, 2004)
The  research was  done to produce o map showing  areas of a high bushfire risk and to create  a statistic  table shov'ing,.for each properfy, the totsl area with a high bushfire  risk and proportion ofthe  high bushfire risk area lo the total area ofthe  property.The research was carried  out in Pooncarie  region, south western New South Wales Australia, which is best described as an area of semiarid rangeland.  GIS (Geographic Information  Systems)  spatiul analysis was conducted  usingfour  coverages: Iand system,  roads, bores, and property, including their coruesponding attribute  data. Bffiring technique  and overlay  operations  for spatial analysis were done using Arcllnfo  GIS sofrware  based on some determined  criteria, yielding a map showing  areas of a high bushfire  risk. Five properties  had the highest proportion of their land being identified as with a high bushfire risk. Keywords: bushfire, geographic  information ststenn,  buffering, spatia\ analysis.